2013
DOI: 10.1128/aem.03557-12
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Genotypes Present in Oysters and in Effluent from a Wastewater Treatment Plant during the Seasonal Peak of Infections in Ireland in 2010

Abstract: We determined norovirus (NoV) concentrations in effluent from a wastewater treatment plant and in oysters during the peak period of laboratory-confirmed cases of NoV infection in Ireland in 2010 (January to March). Weekly samples of influent, secondary treated effluent, and oysters were analyzed using real-time quantitative reverse transcription-PCR for NoV genogroup I (GI) and genogroup II (GII). The mean concentration of NoV GII (5.87 × 104genome copies 100 ml−1) in influent wastewater was significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…The concentration of NoV GII in the influent was higher than that of GI, which is in accordance with previous reports and epidemiological trends in the United States and globally (3,8,(35)(36)(37)(38). Epidemiological data in the United States and worldwide have shown that NoV outbreaks peak in the colder winter months, with 55% of the cases in the United States occurring in December to February (35,39), and is in agreement with our observation of high NoV GII densities (5.6 log 10 GC/100 ml) in the influent in November to March and with previous reports (3, 37, 40, 41).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The concentration of NoV GII in the influent was higher than that of GI, which is in accordance with previous reports and epidemiological trends in the United States and globally (3,8,(35)(36)(37)(38). Epidemiological data in the United States and worldwide have shown that NoV outbreaks peak in the colder winter months, with 55% of the cases in the United States occurring in December to February (35,39), and is in agreement with our observation of high NoV GII densities (5.6 log 10 GC/100 ml) in the influent in November to March and with previous reports (3, 37, 40, 41).…”
Section: Discussionsupporting
confidence: 81%
“…We did not identify any GI.6 strains; however, it was the dominant GI genotype isolated from 49 WTTP in the Netherlands (44). GI.4 was the dominant genotype in wastewater effluent, and oysters were contaminated with wastewater in Ireland (38); however, we found this genotype only in January in 17% (3/18) of the influent and 5% (1/18) of the effluent clones. The GI.1 genotype was the dominant NoV strain in the influent; however, this genotype has been associated with less than 1% of the outbreaks in the United States during 2009 to 2013, as opposed to GI.6 (49.7%), GI.3 (24.6%), and GI.4 (9.9%) (46).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations